Effects of Fed Announcements on Emerging Markets: What Determines Financial Market Reactions?. Issue Volume 66:Issues 4(2018) (December 2018) - Mishra, Prachi; N'Diaye, Papa; Nguyen, Lam
Abstract This paper analyzes market reactions to the 2013–2014 Fed announcements related to the tapering of asset purchases and examines how these reactions are influenced by financial depth. The study focuses on long-term government bond yields and uses daily data for all emerging markets. Controlling for all time-invariant country characteristics as well as time-varying macroeconomic fundamentals (changes in current account, fiscal balance, GDP growth, and inflation), countries with deeper domestic financial markets (as measured by higher bank credit, M2, M3, or stock market capitalization) experienced smaller increases in government bond yields during 4-day windows around Federal Open Market Committee announcements related to tapering. Countries with better macroeconomic fundamentals (measured by improvements in current account, fiscal balance, and GDP growth) also experienced smaller increases in government bond yields around such episodes.